1999
DOI: 10.1093/ajcn/69.5.937
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term intake of retinol on selected clinical and laboratory indexes

Abstract: Background:Chemopreventive agents developed to be used in a moderate-risk but otherwise healthy population need to be both efficacious and to have minimal adverse effects. Objective: The objective of this study was to evaluate the adverse effects of long-term retinol intake in a skin cancer chemoprevention trial in a large population at moderate risk for skin cancer. Design: Participants (n = 2297) were randomly assigned to receive retinol [7576 retinol equivalents (RE), or 25 000 IU] or a placebo daily. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 26 publications
3
20
0
Order By: Relevance
“…Cartmel et al (1999) suggested from their results that moderate concentrations of vitamin A may have an adverse effect on the LDL/HDL ratio: the LDL/HDL ratio increased slightly from 3.071.08 to 3.371.18 (NS) in the retinol group and from 3.171.17 to 3.271.14 (NS) in the placebo group in conjunction with a relative lowering of HDL and a relative increase in LDL in the retinol compared to the placebo group. Lowering of HDL and an increase in LDL has also been reported with use of some synthetic retinoids (Vahlquist et al, 1985;Marsden, 1986;Tangrea et al, 1993); such a change in LDL/HDL ratio increases risk of ischemic heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Cartmel et al (1999) suggested from their results that moderate concentrations of vitamin A may have an adverse effect on the LDL/HDL ratio: the LDL/HDL ratio increased slightly from 3.071.08 to 3.371.18 (NS) in the retinol group and from 3.171.17 to 3.271.14 (NS) in the placebo group in conjunction with a relative lowering of HDL and a relative increase in LDL in the retinol compared to the placebo group. Lowering of HDL and an increase in LDL has also been reported with use of some synthetic retinoids (Vahlquist et al, 1985;Marsden, 1986;Tangrea et al, 1993); such a change in LDL/HDL ratio increases risk of ischemic heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Kushi et al (63) found that supplemental vitamin A was not associated with a lower risk of dying from coronary disease. Cartmel et al (64) evaluated the adverse effects of long-term systemic retinol intake. The median follow-up time was 3.8 yr.…”
Section: Carotenoids and Cardiovascular Disease (Cvd)mentioning
confidence: 99%
“…After 49 mon of follow-up, triacylglycerol was 11% higher, cholesterol was 3% higher, and HDL was 1% lower in the retinal group than in the placebo group. Because a 1% increase in cholesterol concentration has been reported to be associated with a 2% increase in coronary heart disease (64), the interpretation of the effects of long-term ingestion of 7,576 RE vitamin A/d should be approached cautiously. Further studies are needed to confirm this finding.…”
Section: Carotenoids and Cardiovascular Disease (Cvd)mentioning
confidence: 99%
“…In one large Phase III trial of orally administered retinol (25,000 IU/day for up to 5 years) in 2,297 randomized participants with evidence of moderate to severe actinic keratosis, the vitamin A intervention was associated with minimal toxicity (i.e., mild elevation of serum lipids) and a 32% reduction in the risk of squamous cell carcinoma (1,4). Having previously shown that vitamin A doses as high as 300,000 IU/day were well tolerated for up to 1 year in patients with advanced cancers, we were interested in evaluating the safety and efficacy of retinyl palmitate doses in the intermediate range of 25,000 -75,000 IU/day in the treatment of patients with sun-damaged skin (5).…”
Section: Introductionmentioning
confidence: 99%